Adequacy of immediate nursing care received by newborn babies in labor room. - Thapa, Basanti (2000)
ABSTRACT: infection prevention was also found moderately adequate for 62.1% . In this study, it was found that early initiation of breast feeding was inadequate of 0.5%, physical assessment scored by 36.3%, and report keeping system only 1.4%. The comparative analysis between the ANM and basic level students, on the aspect of care was 41.5% and 43.7% respectively and which is of inadequate care received by newborn babies. The study also revealed that the nursing care received by newborn varied on the experience of ANM, the babies received 41.1% care from less than two years of experienced staff and only 33.3% of care was from more than 2 years of experience staff. There is no significant difference between the care by chi square test of the two groups. The result of this study provides information to those who work in the field of women's health and development and all health care facilities about the importance of neonatal care practice, to maintain staff skills, ensure the availability of functioning equipment and supply. • The findings of the study provide feedback to nurses on the immediate nursing care requirement to the newborn babies. • It helps to highlight the strengths and weaknesses of the areas of nursing care received by newborn babies soon after the birth. • It also reveals the needs for continuing education of the nursing staff.